Negative social experiences and self-esteem in people with schizophrenia - Eka Putri, Dewi; Freska, Windy (Jurnal Konseling dan Pendidikan, 2024)
Schizophrenia, a chronic mental health condition, is often compounded by social stigma and discrimination, which can significantly affect the well-being of individuals diagnosed with the disorder. This study explores the impact of negative social experiences and responses to discrimination on the self-esteem of individuals with schizophrenia, a population often affected by social stigma that harms their psychological well-being. Using a quantitative correlational design, the study aimed to analyze the relationship between these variables. The research was conducted in 2023 at the Adult Polyclinic RSJ Prof. HB Saanin Padang, involving 341 schizophrenia patients. Data were collected using a validated questionnaire that assessed negative social experiences, responses to discrimination, and self-esteem, with data analyzed using Pearson's correlation test. The results indicated a significant relationship between both negative social experiences (r = 0.032 p < 0.05) and responses to discrimination (r = 0.045, p < 0.05) with self-esteem. These findings contribute to the growing body of literature on stigma and self-esteem in schizophrenia, highlighting the detrimental effects of social discrimination on mental health. Based on these results, it is recommended that psychological interventions for schizophrenia sufferers incorporate strategies to reduce stigma and address discrimination, which could improve their self-esteem and overall quality of life.